2009
DOI: 10.1063/1.3082099
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelastic/piezoelectric laminated structures for tunable remote contactless magnetic sensing and energy harvesting

Abstract: Articles you may be interested inFluoroethylenepropylene ferroelectret films with cross-tunnel structure for piezoelectric transducers and micro energy harvesters J. Appl. Phys. 116, 074109 (2014); 10.1063/1.4893367 High-sensitivity laminated magnetoelectric sensors without bias in composite of positive/negative giant magnetostrictive materials and piezoelectric single crystals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Broadband operation at resonance can be achieved by tuning the resonance frequency, either by changing the mass or stiffness of a free cantilever structure 14 or by adjusting the mechanical stress of a bridge-like structure. [15][16][17] For example, Finkel et al achieved a full octave of tuning capability by utilizing a uni-axial stress tuning approach in double-clamped ME structures. 18 As will be seen, the magnetic field frequency dependence of tunable resonators can be used for near-DC magnetic field sensing.…”
mentioning
confidence: 99%
“…Broadband operation at resonance can be achieved by tuning the resonance frequency, either by changing the mass or stiffness of a free cantilever structure 14 or by adjusting the mechanical stress of a bridge-like structure. [15][16][17] For example, Finkel et al achieved a full octave of tuning capability by utilizing a uni-axial stress tuning approach in double-clamped ME structures. 18 As will be seen, the magnetic field frequency dependence of tunable resonators can be used for near-DC magnetic field sensing.…”
mentioning
confidence: 99%
“…With the growing demands in the market of low power wireless sensor nodes and electronics devices, various energy harvesters utilizing ambient mechanical vibrations to generate electricity have been investigated (Dong et al 2008;Bowers and Arnold 2008;Beeby et al 2006Beeby et al , 2007Lo and Tai 2008;Neil et al 2002;Roundy and Wright 2004;Finkel et al 2009;Marinkovic and Koser 2009;Hatipoglu and Urey 2010). Several scavenging techniques based on electrostatic, piezoelectric and electromagnetic transduction mechanism have been reviewed (Beeby et al 2006;Arnold 2007;Zhu et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that the energy level obtained by these techniques is sufficient to power-up various types of microsystems (Kulah and Najafi 2008). In order to obtain the maximum energy and power output, the mainstream energy harvesting mechanisms work on resonant mode approach (Dong et al 2008;Beeby et al 2007;Neil et al 2002;Roundy and Wright 2004;Finkel et al 2009), because the excited amplitude reaches its maximum when the mechanical resonant frequency of movable part of energy harvester matches with the ambient vibration frequency. In fact, the vibration frequency of ambient available vibration sources is random and varies from one case to the others (Roundy et al 2003;Mitcheson et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, we have demonstrated tunability of the transverse resonance frequency of ME bimorph by prestressing the double-side clamped ͑fixed end boundary conditions͒ ME structures and controlling the frequency shift by external magnetic field by forced magnetostrictive stresses. [14][15][16] Here, we show that it is possible to achieve stable enhancement in ␣ ME in a controllable resonant transverse fundamental mode by implementing this tunable approach. 16 It is confirmed that the bandwidth of the ME resonant response can be effectively broadened by resonance tuning via magnetic, electrical, or stress field.…”
Section: -12mentioning
confidence: 99%
“…The fabrication of Fe-Ni ͑2 ϫ 50ϫ 0.050 mm 3 ͒ / PVDF ͑0.027 mm͒ laminate bimorphs have also been reported; 14 however, the current samples were made with the longitudinal axis normal to the rolling direction of the Fe-Ni film in order to maximize the effective magnetostriction .…”
Section: 1113mentioning
confidence: 99%